The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.3390/molecules24010029
|View full text |Cite
|
Sign up to set email alerts
|

Metal- and Oxidant-Free Photoinduced Aromatic Trifluoromethylation Performed in Aerated Gel Media: Determining the Effects on Yield and Selectivity

Abstract: In this work we have investigated the potential benefits of using supramolecular gel networks as reaction media to carry out air-sensitive metal-free light-induced trifluoromethylation of six-membered (hetero)arenes under aerobic conditions. This reaction was performed at room temperature (RT) using sodium triflinate (CF3SO2Na, Langlois’ reagent) as a source of radicals and diacetyl as electron donor. The effects of confinement in gel media, concentration of reactants, and type of light source on yield and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Polyamide‐based supramolecular gels were also applied as reaction media to carry out air‐sensitive and metal‐free, light‐induced trifluoromethylation of six‐membered (hetero)arenes under aerobic conditions (Scheme 36). [48] The reaction was performed at room temperature using sodium triflinate as a source of radicals and diacetyl as electron donor. It was observed that different variables influenced the yields and selectivity of the reaction, especially the type of gelator and its concentration.…”
Section: Photocatalysismentioning
confidence: 99%
“…Polyamide‐based supramolecular gels were also applied as reaction media to carry out air‐sensitive and metal‐free, light‐induced trifluoromethylation of six‐membered (hetero)arenes under aerobic conditions (Scheme 36). [48] The reaction was performed at room temperature using sodium triflinate as a source of radicals and diacetyl as electron donor. It was observed that different variables influenced the yields and selectivity of the reaction, especially the type of gelator and its concentration.…”
Section: Photocatalysismentioning
confidence: 99%
“…We have recently described our preliminary results regarding a similar trifluoromethylation reaction of unactivated six-membered (hetero)arenes under aerobic conditions using supramolecular gels as confining media. 48 When the reaction was performed under inert atmosphere conditions with vigorous stirring, the overall yield was 96% favoring the monosubstituted product (i.e., monosubstituted 79%, disubstituted 17%, Figure 13). The overall yield decreased to only 37% when the reaction was carried out under aerobic conditions.…”
Section: ■ Photoreductionmentioning
confidence: 96%
“…Thus, it can be comfortably argued that photoredox catalysis processes in supramolecular gels can emerge as an advanced methodology for the synthesis of halogenated drug molecules under aerobic conditions. 130 In a recent report, Yang et al demonstrated multicomponent supramolecular gels from two types of porphyrin dyes, TCPP/ THPP and an L-glutamic acid based amide gelator (G4) (Figure 29). 131 J-aggregation of porphyrin derivatives and protonation under neutral conditions within DFM gels led to enhanced absorption in visible wavelengths.…”
Section: Photoredox Catalysis Processes Withinmentioning
confidence: 99%
“…The gel network decreased the diffusion of O 2 , preventing fast deactivation of the excited species generated upon photoexcitation of the catalyst. Thus, it can be comfortably argued that photoredox catalysis processes in supramolecular gels can emerge as an advanced methodology for the synthesis of halogenated drug molecules under aerobic conditions …”
Section: Photoredox Catalysis Processes Within Supramolecular Gel Net...mentioning
confidence: 99%